RETRACTED : The Role of Trichoderma sp. as a Biocontrol Agent in Suppression of Root Rot Disease and Soybean Plant Biostimulants - Maknunin, Lu'lu'il; Abadi, Abdul Latief; Choliq, Fery Abdul (Journal of Tropical Plant Protection, 2025)
This article has been retracted at the request of the author. The author has published the article in the Jurnal Fitopatologi Indonesia (JFI).